(untitled) (Texas Journal of Medical Science, 2023)
Researches at 450 women with intrauterous contraception are conducted. The interrelation between carrying terms of intrauterous contraceptives and iron deficiency is studied. Application intrauterous contraceptives depending on terms of their carrying led to various degrees of iron deficiency. It demands dynamic control over indicators of red blood and carrying out of preventive treatment of an anaemia at women